The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1186/s12906-017-2029-0
|View full text |Cite
|
Sign up to set email alerts
|

Coptis Chinensis affects the function of glioma cells through the down-regulation of phosphorylation of STAT3 by reducing HDAC3

Abstract: BackgroundGlioma remains the most common cause of brain cancer-related mortality. Glioma accounts for 50–60% of brain cancer. Due to their low toxicity and infrequent side effects, traditional herbs have been increasingly popular. Coptis Chinensis is commonly used in cancer treatment in combination with other Chinese Medicine herbs. However, little is known about its biological functions and mechanisms in glioma cells.MethodsIn this study, the anti-glioma cell effect of Coptis Chinensis was determined using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…C. Rhizoma extract induces glioma cell apoptosis. Under treatment with C. Rhizoma extract, the expression of proteins associated with apoptosis was altered and involved the reduction of total Caspase-3 and induced cleavage Caspase-3 ( Li J. et al, 2017 ). The water extracts of C. Rhizoma exerted apoptotic effects in immortalized human oral keratinocytes through the mitochondrial signaling pathway, represented by mitochondrial cytochrome-C release and Caspase-3 activation ( Lee et al, 2006 ).…”
Section: Antitumor Effects and Corresponding Mechanismsmentioning
confidence: 99%
“…C. Rhizoma extract induces glioma cell apoptosis. Under treatment with C. Rhizoma extract, the expression of proteins associated with apoptosis was altered and involved the reduction of total Caspase-3 and induced cleavage Caspase-3 ( Li J. et al, 2017 ). The water extracts of C. Rhizoma exerted apoptotic effects in immortalized human oral keratinocytes through the mitochondrial signaling pathway, represented by mitochondrial cytochrome-C release and Caspase-3 activation ( Lee et al, 2006 ).…”
Section: Antitumor Effects and Corresponding Mechanismsmentioning
confidence: 99%
“…Many studies have shown that Coptis Rhizoma and its extract have obvious anti-glioma effects. In vivo and in vitro experiments have shown that coptis chinensis granules inhibited the proliferation of glioma cells, arrested cell cycle in G2/M phase and induced apoptosis via the down-regulation of photosynthesis of STAT3 by reducing HDAC3 (68). Berberine (Figure 2M) not only significantly inhibited inflammatory cytokine Caspase-1 activation via ERK1/2 signaling and subsequently decreased production of IL-1β and IL-18 in U251 and U87 cells, but inhibited the process of EMT through upregulating the protein expression of β-catenin, α-catenin, and downregulating the protein expression of vimentin, α-SMA, so, it could effectively inhibit glioma cell proliferation, invasion and metastasis (69).…”
Section: Coptis Rhizomamentioning
confidence: 99%
“…In addition, efforts have been made to examine the potential therapeutic and biological functions of CC, not as a single compound, but as multi-compounds, for cancer treatment. CC has been shown to exert an anticancer effect through the downregulation of signal transducer and activator of transcription (STAT)2 phosphorylation by reducing the level of histone deacetylase 2 (HDAC2) in glioma cells and inhibiting hepatocellular carcinoma cell growth through non-steroidal anti-inflammatory drug (NSAID) activated gene (NAG-1) activation (14,15). In non-small cell lung cancer (NSCLC) cells, CC has been shown to inhibit growth and metastasis, and to induce cell apoptosis (16).…”
Section: Cancer Cell-specific Anticancer Effects Of Coptis Chinensis On Gefitinib-resistant Lung Cancer Cells Are Mediated Through the Sumentioning
confidence: 99%